2021
DOI: 10.1007/s00338-020-02043-0
|View full text |Cite
|
Sign up to set email alerts
|

Polyp bailout and reattachment of the abundant Caribbean octocoral Eunicea flexuosa

Abstract: Anthozoans exhibit great plasticity in their responses to stressful conditions, including decreasing individual size, detaching from the substratum and relocating, and releasing endosymbiotic microalgae. Another response to stress used by some colonial anthozoans is polyp bailout, in which the coenenchyme breaks down and individual polyps detach from the colony. We observed polyp bailout in the common Caribbean gorgonian Eunicea flexuosa after eight hours of aerial exposure. After nine days, 28% of bailed-out … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Polyp bailout, by contrast, refers to the escape of polyps without calices from a parent colony in response to acute environmental stress (e.g. Sammarco 1982;Kružić 2007;Capel et al 2014;Serrano et al 2018) and was also observed for octocoral species (Rakka et al 2019;Wells and Tonra 2020). Thus, polyp bail-out provides a route of escape to new locations for possible resettlement.…”
Section: Introductionmentioning
confidence: 99%
“…Polyp bailout, by contrast, refers to the escape of polyps without calices from a parent colony in response to acute environmental stress (e.g. Sammarco 1982;Kružić 2007;Capel et al 2014;Serrano et al 2018) and was also observed for octocoral species (Rakka et al 2019;Wells and Tonra 2020). Thus, polyp bail-out provides a route of escape to new locations for possible resettlement.…”
Section: Introductionmentioning
confidence: 99%
“…Though a range of asexual reproductive strategies has been documented in corals, including colony fragmentation [26], polyp bail-out [11,27] and the asexual production of larvae [12,28,29], the unique ecological context of the mangrove population studied here implicates asexual production of planula larvae as the only plausible mode of clonal reproduction. Given that individuals are growing on prop-roots suspended over a mud/silt bottom, reproduction via colony fragmentation, which is thought to be a common mode of asexual reproduction in P. divaricata [30], would invariably result in mortality because colony fragments cannot re-adhere to the prop-roots, and those that fall to the bottom are quickly submerged in soft sediment, a phenomenon that we have repeatedly observed in the field (figure 1 d ).…”
Section: Resultsmentioning
confidence: 99%
“…Given that individuals are growing on prop-roots suspended over a mud/silt bottom, reproduction via colony fragmentation, which is thought to be a common mode of asexual reproduction in P. divaricata [30], would invariably result in mortality because colony fragments cannot re-adhere to the prop-roots, and those that fall to the bottom are quickly submerged in soft sediment, a phenomenon that we have repeatedly observed in the field (figure 1 d ). Similarly, isolated individual polyps produced by polyp bail-out, a mechanism of asexual reproduction that has never been reported in poritid corals, would be unable to colonize prop-roots and would fall to the mud bottom because they are ‘slightly negatively buoyant’, with limited mobility [11,27]. By contrast, planulae are capable of directed swimming, searching behaviour and settlement, and asexual planulation has been reported in another Porites species [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zooxanthellae density and Chl a contentThis study showed that the number of zooxanthellae and the Chl a content were relatively stable in the Y and Z, while group X showed a signi cant downward trend. Unsuitable photoperiod might cause zooxanthellae to escape from the polyps to avoid the adverse environment, resulting in a decline in the number of zooxanthellae and the content of Chl a(Nakamura et al 2017;Wells et al 2021). In addition, the photosynthetic e ciency of the coral-symbiotic zooxanthellae would decrease when illumination time was insu cient, thus affecting the growth of corals at the end.…”
mentioning
confidence: 99%